2002
DOI: 10.1074/jbc.m104396200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent Cellular Localization and Thermoprotective Role of Heat Shock Protein 25 in Hippocampal Progenitor Cells

Abstract: The present study examined phosphorylation-dependent cellular localization and the thermoprotective role of heat shock protein (HSP) 25 in hippocampal HiB5 cells. HSP25 was induced and phosphorylated by heat shock (at 43°C for 3 h). HSP25, which was located in the cytoplasm in the normal condition, translocated into the nucleus after the heat shock. Transfection experiments with hsp27 mutants in which specific serine phosphorylation residues (Ser 78 and Ser 82 ) were substituted with alanines or aspartic acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
103
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 41 publications
9
103
0
Order By: Relevance
“…In human keratinocyte cultures, inhibitors of p38MAPK prevented PV IgG-induced phosphorylation of HSP27 and, more importantly, prevented the early cytoskeletal changes associated with loss of cell-cell adhesion (14). We suggested that the observed effects may be important to the mechanism of PV IgG-induced acantholysis because HSP27 has been shown to regulate both actin (17)(18)(19) and intermediate filaments (20,21). Furthermore, p38MAPK-mediated phosphorylation of HSP27 had been shown to regulate the cytoskeleton (22)(23)(24).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In human keratinocyte cultures, inhibitors of p38MAPK prevented PV IgG-induced phosphorylation of HSP27 and, more importantly, prevented the early cytoskeletal changes associated with loss of cell-cell adhesion (14). We suggested that the observed effects may be important to the mechanism of PV IgG-induced acantholysis because HSP27 has been shown to regulate both actin (17)(18)(19) and intermediate filaments (20,21). Furthermore, p38MAPK-mediated phosphorylation of HSP27 had been shown to regulate the cytoskeleton (22)(23)(24).…”
mentioning
confidence: 89%
“…HSP27 and the related murine protein HSP25 function in signal transduction where they may regulate the actin (17)(18)(19) and intermediate filament (20,21) cytoskeleton. Additionally, p38MAPK-mediated phosphorylation of HSP27 modulates its regulation of the cytoskeleton (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…For Hsp27, the extent of phosphorylation is high (5,14), and phosphorylation is required for thermotolerance (19,49,50). For ␣B-crystallin, the extent of phosphorylation is low (6,13), and the role of phosphorylation in thermotolerance is not known.…”
Section: Shsps Protect Cap-dependent Translation After Heat Shockmentioning
confidence: 99%
“…For Hsp27 and ␣B-crystallin, phosphorylation has been shown to prevent complex formation in vitro (15)(16)(17), resulting in significant decrease in chaperone activity (16 -18). Phosphorylationmimicked Hsp27 protects cells from heat stress but not from oxidative stress (16,19,20).…”
mentioning
confidence: 99%
“…Phosphorylation appears essential for protecting against heat shock-induced loss of clonogenic activity. It is also essential for protection against the toxic action of a number of anticancer drugs (6,27,38). In contrast, the non-phosphorylated and oligomeric species of high molecular weight are better at protecting against tumor necrosis factor-␣ or oxidative stress, suggesting different modes of protection of Hsp27 against different stresses (39,40).…”
mentioning
confidence: 99%